1999
DOI: 10.1111/j.1528-1157.1999.tb01992.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis After Resection of Ganglioglioma or DNET: Evidence for an Association

Abstract: Summary:Purpose: David Taylor and Murray Falconer suggested that some patients may develop a psychotic illness after resection of a ganglioglioma that led to intractable seizures. They implied that the mechanism of this association remained unclear. This concept is currently not universally accepted (M. Trimble, personal communication).Methods: We studied six children or young adults from four centers who developed psychosis after resection of a ganglioglioma or dysembryoplastic neuroepithelioma (DNET).Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(35 citation statements)
references
References 12 publications
0
28
0
5
Order By: Relevance
“…Entretanto, ambos apresentaram piora comportamental importante. Andermann et al 27 sugerem que problemas psíquicos e comportamentais podem ocorrer em sujeitos submetidos à ressecção de tumores em lobo temporal e, por apresentarem bom resultado quanto ao controle das crises, aventam que o mecanismo de "normalização forçada" talvez seja o responsável por este fenômeno. As pacientes 1 e 9 apresentaram atraso de linguagem na avaliação pré-cirúrgica, ambas com epilepsia de lobo temporal esquerdo, coincidindo com os achados de Lendt et al 5 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Entretanto, ambos apresentaram piora comportamental importante. Andermann et al 27 sugerem que problemas psíquicos e comportamentais podem ocorrer em sujeitos submetidos à ressecção de tumores em lobo temporal e, por apresentarem bom resultado quanto ao controle das crises, aventam que o mecanismo de "normalização forçada" talvez seja o responsável por este fenômeno. As pacientes 1 e 9 apresentaram atraso de linguagem na avaliação pré-cirúrgica, ambas com epilepsia de lobo temporal esquerdo, coincidindo com os achados de Lendt et al 5 .…”
Section: Discussionunclassified
“…A não alteração significativa no QI pela maioria dos sujeitos após a cirurgia é congruente com outros estudos 6,27,28 .…”
Section: Discussionunclassified
“…Andermann et al reported six patients from four centers who experienced a de novo psychotic disorder and estimated a risk of 2.5 % for the development of de novo psychosis (1 in 39) in patients with this type of lesion who undergo an ATL [ 27 ].…”
Section: Postsurgical Psychotic Complicationsmentioning
confidence: 97%
“…Firlik et al [92]reported the concurrence of ganglioglioma and Rasmussen’s encephalitis in a 4-year-old boy who underwent a hemispherectomy with favorable results. Andermann et al [93]reported a small group of children from several different institutions that experienced a paranoid schizophrenic psychosis with depressive features after removal of gangliogliomas. This occurred in 1 of 39 resections and not in other types of lesional epilepsy surgery in the authors’ vast collective experience, indicating that this is a real, but unusual complication of resection.…”
Section: Gangliogliomas and Ganglioneuromasmentioning
confidence: 99%